Associations of functional connectivity and walking performance in multiple sclerosis. (August 2018) - Bollaert, Rachel E.; Poe, Kyle; Hubbard, Elizabeth A.; Motl, Robert W.; Pilutti, Lara A.; Johnson, Curtis L.; Sutton, Bradley P.
Abstract: Background: Persons with multiple sclerosis (MS) often demonstrate impaired walking performance, and neuroimaging methods such as resting state functional connectivity (RSFC) may support a link between central nervous system damage and disruptions in walking. Objectives: This study examined associations between RSFC in cortical networks and walking performance in persons with MS. Methods: 29 persons with MS underwent 3-T brain magnetic resonance imaging (MRI) and we computed RSFC among 68 Gy matter regions of interest in the brain. Participants completed the Timed 25-foot Walk as a measure of walking performance. We examined associations using partial Pearson product-moment correlation analyses ( r ), controlling for age. Results: There were eight cortical brain regions that were significantly associated with the T25FW, including the left parahippocampal gyrus and transverse temporal gyrus, and the right fusiform gyrus, inferior temporal gyrus, lingual gyrus, pericalcarine cortex, superior temporal gyrus, and transverse temporal gyrus. Conclusions: We provide novel evidence that RSFC can be a valuable tool to monitor the motor and non-motor networks impacted in MS that relate to declines in motor impairment. RSFC may identify critical nodes involved in a range of motor tasks such as walking that can be more sensitive to disruption by MS. Highlights: RSFC of brain regions is associated with walking performance in persons with MS. The identified brain regions include motor and non-motor networks. RSFC might help identify critical nodes involved in motor tasks such as walking.